EFEKTIVITAS PENERIMAAN PAJAK KENDARAAN BERMOTOR PADA PUSAT PENGELOLAAN PENDAPATAN DAERAH KOTA CIMAHI (PERIODE 2016-2020) - Rum, Avid Inang; Oktaviani, Rina (Unit Penelitian dan Pengabdian kepada Masyarakat Politeknik TEDC Bandung Jl. Pesantren Km 2 Cibabat Cimahi Utara, Cimahi 40513 Jawa Barat, Indonesia, 2023)
The purpose of this research is to find out how the target, realization, and effectiveness of motor vehicle tax revenues at the Pusat Pengelolaan Pendapatan Daerah Wilayah Kota Cimahi (2016-2020 period). The method used in this research uses a descriptive method with a qualitative approach. Data collection techniques in this research were carried out by observation, interview, literature study, and documentation study. The data obtained are processed by means of data reduction, data presentation, and drawing conclusions. The types and sources of data in this research are data on motorized vehicles in Cimahi City in 2016-2020, as well as data on targets and realization of motor vehicle tax revenues for 2016-2020.The results showed that the effectiveness of motor vehicle tax receipts at the PusatPengelolaan Pendapatan Daerah Wilayah Kota Cimahi for the 2016-2020 period fluctuated. The highest percentage of achievement was in 2017 which was 104,93%, and the lowest percentage of achievement was in 2020, which was 83,16%. The increase and decrease in effectiveness from 2016-2020 ranged from 0,01% to 16,87%. Although the percentage of achievement fluctuated, in terms of revenue in 2016-2019 it always increased, except in 2020 it decreased.